Direct measurement of ion chamber correction factors, kQ and kB, in a 7 MV MRI-linac. (21st May 2019) - de Prez, Leon; Woodings, Simon; de Pooter, Jacco; van Asselen, Bram; Wolthaus, Jochem; Jansen, Bartel; Raaymakers, Bas
Abstract: The output of MRI-integrated photon therapy (MRgXT) devices is measured in terms of absorbed dose to water, D w . Traditionally this is done with reference type ion chambers calibrated in a beam quality Q 0 without magnetic field. To correct the ion chamber response for the application in the magnetic field, a factor needs to be applied that corrects for both beam quality Q and the presence of the magnetic field B, k Q, B . This can be expressed as the product of k Q, without magnetic field, and ion chamber magnetic field correction, k B . k B depends on the magnetic field strength and its direction, the direction of the beam and the orientation and type of the ion chamber. In this study, for the first time, both k Q and k B were measured directly for six waterproof ion chambers (3  ×  PTW 30013 and 3  ×  IBA FC65-G) in a pre-clinical 7 MV MRI-linac at 0 T and at 1.5 T. Measurements were done with the only available primary standard built for this purpose, a water calorimeter. Resulting k Q factors for PTW and IBA chambers were 0.985(5) and 0.990(4), respectively. k B factors were measured with the chambers in antiparallel direction to the magnetic field (|| 180°), and perpendicular direction (⊥  −90°). k B|| and k B⊥ for the PTW chambers were 0.985(6) and 0.963(4), respectively and for IBA chambers 0.995(4) and 0.956(4). Agreement with the available literature values was shown, partly caused by the relatively large standard deviation (SD) in those values. The values in this study are currently the only available measured values for k Q and k B in an MRI-linac that are directly linked to the international traceability framework for the quantity absorbed dose to water, D w .